Envelhecer com Passione: a telenovela na vida de idosas das classes populares - Wottrich, Laura Hastenpflug (2011)
This research aims at understanding the relationships among the representation of elderlihood conveyed in a telenovela of a prime time and its appropriation by elderly women of popular classes. The objective is to understand how telenovela builds representations of elderlihood as well as how such representations are taken by receptors as concerns building their identities through mediation of gender and social class. Theoretically, it is based on the cultural studies, on latin-american reflections about mediation proposed by Martín-Barbero and on the intersection between studies about elderlihood and media. As for the method, theories of the Codification/Decodification model, proposed by Stuart Hall, and the Culture Communicative Mediations method proposed by Martín-Barbero are articulated. Regarding production, an analysis of elderly representations portrayed in telenovela Passione and reflections about the dynamics of the production of the plot were accomplished. Reception is studied through six elderly women, among 63 to 76 years old, from popular classes, living in Santa Maria-RS. Such study is a critical ethnography of reception. Observation of the domestic space, with registers in the field journal, were used as techniques, along with watching telenovela together with four of those women, exploratory interviews and semistructured/closed interviews. Results point out that telenovela has an important participation on the process of building elderlihood of the receptors, facing a context of wide destabilizations on the ways of representing and living such period of life. Passione, although endorsing the dominant representations, brings significant spaces for negotiation and presents opposing codifications of elderlihood, especially as regards the dimensions of family and affective life/sexuality. Appropriation of the receptors are pervaded by mediations of class and of gender. The class defines a more oppressive experience of the feminine condition, marked by a sexist education, sexual division of labor and interference over their lives, which pervade the ways they mean their elderlihood. Entering elderlihood, for once, seems to turn their traditional representations of elderlihood into an unstable condition. Such dynamics configures their representations of elderlihood and is present on the reception of telenovela, where two different matrixes of reading were found, configuring a negotiated decodification. In general terms, they endorse the dominant codifications of elderlihood. When thinking about the plot in relation to themselves, as concerns identification with the characters, more opposing meanings appear according to more positive meanings of elderlihood that they try to build for themselves.